The influence of midsole horizontal and vertical deformation on soft tissue vibrations and bone acceleration during running - Trama, R.; Wannop, J. W.; Smith, E.; Stefanyshyn, D. J. (Journal of Sports Sciences, 2023)
Increased midsole deformation can limit exposure to high impact and vibration magnitudes while running. The aim of this study was to evaluate the effect of shoes eliciting different midsole deformation on ground reaction forces, heel impact, soft tissue vibrations and bone vibrations. Forty-eight runners performed a 5-min running task on an instrumented treadmill at a self-selected pace with four different shoes. Midsole horizontal and vertical deformations were quantified with relative displacement of seven reflective markers placed on the midsole of the shoe and tracked by eight optoelectronic cameras. Heel impacts, soft tissue and bone vibrations of lower leg muscle groups, sacrum and head were quantified with tri-axial accelerometers. Continuous wavelet transform was used to assess magnitude and frequency of the acceleration data. Linear mixed models and non-parametric one-dimensional regressions between the accelerometer data and shoe deformation were performed. Greater horizontal and vertical deformations decreased the magnitude (up to 4.6% per mm) and frequency (up to 0.6 Hz per mm) of soft tissue vibrations and bone accelerations. Accelerations of the heel, tibia, gastrocnemius medialis and vastus lateralis were more influenced than the sacrum and head. Increasing midsole deformation could therefore mitigate the risk of injury, while increasing running comfort and smoothness.